Quality of life of an institution hypertensive older women long stay - Angelita Visentin; Maria de Fátima Mantovani; Cristiano Caveião; Thatiane Aparecida Mendes; Aline Silvério Neves; Ana Paula Hey (Universidade Federal do Ceará, 2015)
Objective: to identifying the quality of life of hypertensive elderly women´s residents in a long-stay institution. Method: it was conducted a case study, cross-sectional quantitative study. The research began in held in an institution of long stay in the city of Curitiba and data were collected a validated instrument. The study included 12 hypertensive elderly. Results: Showed that, for the elderly, even with intercurrent illness, quality of life remained at average rates when analyzed the different areas. That most contributes in the results was the Social, followed by the Psychological and of the Physical Environment. The majority of older women is satisfied with their quality of life as being cited as well with their body image. Conclusion: nursing work is identifying the factors that interfere conditions of quality of life of older and proposing interventions in institutions.